It's not my fault, it's yours: shame, loss, and the ego ideal in work with adoptive couples. Issue 2 (4th May 2022) - Cregeen, Simon
ABSTRACT: Work with adoptive parents can be complex due to the multiple experiences of loss often carried by the adopted children and by the adoptive parental couple. This paper explores some of the emotional states and dynamics these experiences of loss give rise to, with a specific focus on the parental couple relationship. The case is made for the efficacy of psychotherapy with the couple, the difficulties of managing losses which can generate feelings of shame, and the projective use of blame within the couple and family as a way of evacuating unbearable emotional states. The concept of ego ideal is reviewed, and the need for adoptive couples to relinquish and mourn what is conceptualised as a shared ego ideal. The creation of a more realistic ego ideal is described as a particular aspect of the process of moving from the couple imagining themselves as birth parents, to their aspirations as an adoptive couple. Clinical material is used to illustrate how shame may manifest itself in an adopted child in psychotherapy, and in work with adoptive couples. The inevitably painful nature of mourning, and work with a couple struggling with this, is described.